USAHA ANTISIPASI PERNIKAHAN ILEGAL DI KABUPATEN BENGKALIS (Studi Kasus KUA dan Tokoh Masyarakat Rupat Utara) - Muhammad Al Mansur (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2021)
The large number of cases of illegal marriages in Bengkalis Regency have had a big impact on the community, especially in Rupat Utara District. Illegal marriages are also known as illegal marriages or unregistered marriages, namely a marriage that is carried out under Islamic law without being legally registered at the Office of Religious Affairs (KUA). In almost all villages in Rupat Utarat, illegal marriages were found with a total of 32 cases. The formulation in this research is what are the factors that cause the occurrence of illegal marriages in Rupat Utara District and how to anticipate the occurrence of illegal marriages by the KUA and community leaders in North Rupat. The method used in this research is qualitative research, using normative juridical approaches (positive law) and normative theology (Islamic law), observation, interviews and documentation are used to collect data. The object of this research is the perpetrators of illegal marriages, KUA and community leaders in Rupat Utara. The location of this research is in Rupat Utara District, with interviews with 7 cases of illegal marriage. The results of this study indicate that there are information factors, age limit of marriage, economic and distance factors that cause illegal marriages. KUA and community leaders have made efforts to anticipate illegal marriages very well in Rupat Utara District. Keywords: Anticipation Effort, Illegal Marriage, KUA, Community Leader